Impacts of Side Effects to BNT162b2 and the First Dose of ChAdOx1 Anti-SARS-CoV-2 Vaccination on Work Productivity, the Need for Medical Attention, and Vaccine Acceptance: A Multicenter Survey on Healthcare Workers in Referral Teaching Hospitals in the Republic of Korea - Tark Kim; Se Yoon Park; Shinae Yu; Jung Wan Park; Eunjung Lee; Min Hyok Jeon; Tae Hyong Kim; Eun Ju Choo (Vaccines, 2021)
To establish a successful anti-SARS-CoV-2 vaccination strategy, it is necessary to take possible tradeoffs into account. We conducted a survey on vaccinated healthcare workers (HCWs) inthree referral teaching hospitals in the Republic of Korea. We investigated the frequency of vaccination side effects (SEs), the impact on their work productivity, the need for medical attention, and vaccine acceptance. Three groups of HCWs were surveyed: 1406 who had received the first dose of BNT162b2 (BNT162b2#1), 1168 who had received the second dose of BNT162b2 (BNT162b2#2), and 1679 who had received the first dose of ChAdOx1 (ChAdOx1#1). More SEs and impact on work productivity were reported in ChAdOx1#1 than in the other two groups. However, among individuals aged ≥40 years, no significant difference of absence from work was found between ChAdOx1#1 and BN162b2#2 (4.4%, 31/699 vs. 3.0%, 12/405; p = 0.26), and none were hospitalized. Older HCWs in ChAdOx1#1 showed intention to receive the second dose of the vaccine. Although the incidence of SEs and their impacts were greater after the first dose of ChAdOx1 than BNT162b2 in young people, significant impact of SEs seemed to be rare in individuals aged ≥40 years, regardless of the vaccine they received.